Proposed establishment of a church library in Sto. Cristo Parish, Las Piñas City - Rondero, Charmine Ann G.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
The history of libraries include church libraries. However, the use of church libraries was limited only for the scholars, clergy and the Church authority. Today, church libraries are also available for the public. Unfortunately, this is not yet known in the Philippines especially in the Roman Catholic Church. This is the reason why this study focused on the feasibility of establishing a church library in Sto. Cristo Parish.
Four major factors of feasibility study were utilized, namely: market feasibility, technical feasibility, organizational and management feasibility, and financial feasibility.
Twenty-one (21) item questions were utilized to measure the market feasibility. Thirty-four (34) church workers were the participants in the study. Market study revealed that 100 of the respondents are willing to support the church library in different ways but they thought of fund raising as the major source of maintaining the library.
For technical feasibility, the Parish Priest and Steward if the Commission on Catechetics and Religious Education (ComCARE) were interviewed. It was found out that the possible location of the proposed library was beside the Sacred Heart Hall and the area is approximately 2720 centimeters by 3000 centimeters.
For organizational and management feasibility, the Sto. Cristo Parish Priest and Steward of the Commission on Catechetics and Religious Education (ComCARE) were also interviewed. The study revealed that the recommended organizational structure, library services and library administration (management and staffing) of McMichael (1987) are applicable to the church library setting though some revisions are needed.
For financial feasibility, Sto. Cristo Parish Priest and the Head of the Parish Finance Council (PFC) were interviewed. They both agreed that the major source of financing would be asking for solicitations and donations, and fundraising. The study concludes that the total projected cost is PHP 141,741.03.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Church libraries -- Philippines -- Las Piñas City